PERAN TRI PUSAT PENDIDIKAN DALAM MENGHADAPI PROBLEMATIKA PEMBELAJARAN DARING DI DAERAH 3T - Nila Ulfiaturrohmah; Nurul 'Alimatul Hargianti; Fery Diantoro (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2021)
Writing this article was motivated by a change in the education system in Indonesia due to the Covid-19 virus. Learning that was originally carried out face-to-face has shifted to online learning. This is the impact of efforts to break the chain of the spread of the Covid-19 outbreak by carrying out social restrictions. The implementation of online learning has its own challenges for the world of education, not least for the 3T (Frontier, Outermost, and Disadvantaged) regions, because the implementation is sudden and there has been no thorough preparation from the education provider institutions. The purpose of writing this article is to analyze how the problems of implementing online learning in the 3T area and how to solve these problems. The method in writing this article is the library method. The data collection technique used and used is the search for library sources in books, as well as from various journals related to references about related matters. From the findings of the authors, several online learning problems in the 3T area, including inadequate facilities and infrastructure, the lack of teachers' ability to use technology, low learning motivation among students, and the lack of government reach in distributing aid due to limited road access. These problems can be overcome by synergizing the three education centers. The role of the family in providing assistance to children during the online learning process is very important. In addition, the role of educational institutions and providers of education personnel must be extra in communicating with parents and students in online learning. No less important is the role of the community in helping parents accompany and motivate students in online learning. So, synergy between the three education centers is needed to achieve online learning goals in the 3T area.